Fluorosis dental en estudiantes de 7 a 9 años de edad en la Unidad Educativa Belisario Quevedo del cantón Pujilí de la provincia de Cotopaxi año lectivo 2017-2018 - Rodríguez Cevallos, Nicole Kamila (2017)
The present investigation was carried out in the Educational Unit Belisario Quevedo of the Pujilí Canton. The main objective was to determine the prevalence of dental fluorosis in children between the ages of 7 and 9. The study was observational and transversal, also called a prevalence study. For the purpose of the study, 130 children were seen from urban and rural areas. The intraoral clinical examination was performed, recording the presence or absence of dental fluorosis according to Dean five clinical parameters. Children were classified according to their gender, area of living, the type of drinking water that they consume and the knowledge that they have about this alteration. According to Dean parameters, the study found 81.24 percent of absence of dental fluorosis in children that corresponds to a grade 0; 13.62 percent of questionable fluorosis that corresponds to a grade 1; 4.29 percent of a very mild fluorosis that corresponds to a grade 2; and finally 0.84 percent of a slight fluorosis that corresponds to a grade 3. The study was conducted to XXX women (NUMERO DE NIÑAS) that corresponds to 50.77 percent and XXX men that corresponds to 49.23 percent. 37.69 percent of these children came from urban areas whereas 63.31 percent from the rural area. Regarding the type of water that children consume, the study found that from a total of 150 children, 87 drink drinking water, 33 bottled water, 9 bottled water, 1 drinking water and drought water and nobody drinks drought water only. Before talking to the children about this alteration 32.31 percent did not about it, but after the motivational talks 57.69 percent stated that they understood the problem. In conclusion, 81.24 percent of children between the ages of 7 and 9 did not have dental fluorosis.